The Adoption of the Circumcision Ritual bèkà by the Baka-Pygmies in Southeast Cameroon - Fürniss, Susanne (International Library of African Music, 2008)
In this article, I discuss the borrowing of the circumcision ritual bèkà by the Baka of Cameroon. I will present an in-depth analysis of the ritual system and the music that goes with it, with particular attention to the ritual's actors and their function.
Keywords: Ritual; African Music; Cameroon; Circumcision Ritual